Application of Calcined Green Mussel Shell Powder to Increase Peat Soil Stability Against CBR Values as a Road Pavement Subgrade - Nadhifah Alifia Dewayanti Retnaningrum; Latif Budi Suparma; Suryo Hapsoro Tri Utomo (Universitas Negeri Padang, 2026)
Peat soil has compressible properties, high water content, and low bearing capacity, so it needs to be stabilized to increase its strength as a road pavement subgrade. Peat soil is commonly found in South Sumatra, especially in the Banyuasin II District, Banyuasin Regency, South Sumatera. This study added green mussel shell powder (CaCO3) and calcined mussel shell powder (CaO) as stabilizers with the CBR (California Bearing Ratio) testing method. This test was carried out with variations in the mixture of mussel shell powder (0%, 10%, 20%, 30%) and curing time (0, 3, 7 days), as well as testing physical and mechanical properties such as atterberg limits, specific gravity, sieve analysis, soaked CBR, and unsoaked CBR. Samples with optimal CBR values will be added with CaO (calcined mussel shell powder) 10% to see its effect. Based on the test results, the original peat soil has an unsoaked CBR of 0.65% and a soaked CBR of 0.65%. After the stabilizer was mixed, the optimal variation was found in a mixture of peat soil plus 30% shell powder with 7 days of curing at 13.7%, while for soaked CBR, with a variation of 30% soaking for 4 days at 8.5%. Furthermore, this variation was mixed with calcined shell powder (10%) to see its effect. The test results showed a significant change, the values of unsoaked CBR 35% and soaked CBR 45%.